2014
DOI: 10.1242/jcs.151613
|View full text |Cite
|
Sign up to set email alerts
|

STAG2 promotes error correction in mitosis by regulating kinetochore-microtubule attachments

Abstract: Mutations in the STAG2 gene are present in ,20% of tumors from different tissues of origin. STAG2 encodes a subunit of the cohesin complex, and tumors with loss-of-function mutations are usually aneuploid and display elevated frequencies of lagging chromosomes during anaphase. Lagging chromosomes are a hallmark of chromosomal instability (CIN) arising from persistent errors in kinetochore-microtubule (kMT) attachment. To determine whether the loss of STAG2 increases the rate of formation of kMT attachment erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 67 publications
(76 reference statements)
1
31
0
Order By: Relevance
“…Owing to its interaction with AURKBcontaining chromosomal passenger complex, SGO1 mislocalization impairs error correction. This supports the notion that cohesion defects might cause CIN through stabilization of k-MT attachment errors (Kleyman et al 2014;Tanno et al 2015).…”
Section: Chromosome Cohesion Defectssupporting
confidence: 88%
“…Owing to its interaction with AURKBcontaining chromosomal passenger complex, SGO1 mislocalization impairs error correction. This supports the notion that cohesion defects might cause CIN through stabilization of k-MT attachment errors (Kleyman et al 2014;Tanno et al 2015).…”
Section: Chromosome Cohesion Defectssupporting
confidence: 88%
“…It is likely that the absence of STAG2 expression is not the independent cause of aneuploidy. Furthermore, STAG2 is also essential in the efficient correction of kinetochore-microtubule attachment errors [21], and it is a transcriptional co-activator of NF-kB, suggesting STAG2 could contribute to the control of the expression of genes involved in cell cycle progression [22]. These studies have revealed the reasons for the loss of STAG2 expression driving the process of cancer initiation; however, the mechanism of action of STAG2 loss and its influence on good prognosis need to be clarified in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cohesion defects are known to promote chromosome lagging as shown by studies depleting the Retinoblastoma protein pRb (Manning et al, 2010) or STAG2, a component of the cohesin complex (Kleyman et al, 2014). To test whether cohesion fatigue was occurring during the 8-hour nocodazole treatment used herein, and whether this preferentially affected chromosomes 1 and 2, cells were treated with nocodazole for 8 hours followed by release into the proteasome inhibitor MG132 to delay anaphase but allow chromosome-MT attachments to form.…”
Section: Chromosomes 1 and 2 Are Susceptible To Cohesion Fatigue Durimentioning
confidence: 99%